การใช้เซลลูโลสแบบผลึกระดับจุลภาคที่เตรียมจากเศษผ้าฝ้ายเป็นสารตัวเติมในฟิล์มพีวีซี - ศิริวรรณ สุอุทัย (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
In this research, microcrystalline cellulose (MCC0 was prepared by hydrolyzing waste cotton fabric with 2.5 N HCl at 100 degree Celsius for 30 min. The chemical structure, particle size, morphology and thermal property of the MCC were investigated. The obtained MCC was blended with PVC compound at the amount of 0, 5, 10, 15, 20, 25, and 30 parts per hundred of PVD resin (phr). The mixtures were processed by calendaring method into a film form. The effects of MCC on the mechanical properties, thermal behaviors, morphology, water absorption and biodegradability of the blend films were investigated. The fibrous-shaped particle of MCC was found to posses average particle size of about 40 m. It was found that the tensile strength and Young s modulus of PVC films increased with the increasing amount of MCC. The tear strength also increased with the increasing amount of MCC. However, it decreased as the amount of MCC was higher than 20 phr. In addition, TGA thermogram showed that the thermal behavior of PVD film was insignificantly affected by the addition of MCC. Water absorption and biodegradability of PVD film were enhanced as the amount of MCC was increased. These results indicated that MCC behaves as reinforcing filler in PVC film and also plays an important role in accelerating the biodegradation of PVC film. By considering the ease of processing, the mechanical properties and the biodegradability, the amount of MCC in pvc film should not exceed 20 phr